PENILAIAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN KIMIA MATERI KIMIA UNSUR MENGGUNAKAN MIND MAP DI KELAS XII IPA SEMESTER 1 SMA NEGERI 1 WONOSARI - Anjar Purba Asmara (Lantanida Journal, 2015)
This research is aimed to determine the quality of mind maps which have created by students and to determine the result of students learning in chemistry lesson by using mind map model. The research uses description qualitative method. The population is students of natural science program grade XII at SMA 1 Wonosari years 2013/2014. The sample consists of 96 students at class XII IPA1, XII IPA2, and XII IPA3. The research gives imformation about the quality of student’s mind map which have scored by using mind map scoring rubric and the result of students learning which have tested by giving daily examination. The percentage of very good category, good category, and good enough category is 40%, 40%, and 20% respectively. The average of test value is 80.406, it means that the average value is higher than minimal passing standart. The percentage of student which pass the test is 80.208%. thus the result to be categorized as good level.